2020
DOI: 10.1101/2020.11.03.365270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ACE2-binding interface of SARS-CoV-2 Spike inherently deflects immune recognition

Abstract: The COVID-19 pandemic remains a global threat, and host immunity remains the main mechanism of protection against the disease. The spike protein on the surface of SARS-CoV-2 is a major antigen and its engagement with human ACE2 receptor plays an essential role in viral entry into host cells. Consequently, antibodies targeting the ACE2-interacting surface (ACE2IS) located in the receptor-binding domain (RBD) of the spike protein can neutralize the virus. However, the understanding of immune responses to SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Interestingly, the correlations between neutralization titers and the IgG and IgM datasets to Spike-T and RBD-T, the designed mutant antigens harboring the triple mutants that disrupt the RBD-ACE2 interaction, were among the highest of all isotype-antigen pairs. These results are consistent with our previous results that revealed that the ACE2-interacting surface is not highly immunogenic (Hattori et al, 2021) and with other reports showing that a small fraction of antibodies target this surface of the spike protein (Voss et al, 2021).…”
Section: Assay Design and Validationsupporting
confidence: 94%
See 4 more Smart Citations
“…Interestingly, the correlations between neutralization titers and the IgG and IgM datasets to Spike-T and RBD-T, the designed mutant antigens harboring the triple mutants that disrupt the RBD-ACE2 interaction, were among the highest of all isotype-antigen pairs. These results are consistent with our previous results that revealed that the ACE2-interacting surface is not highly immunogenic (Hattori et al, 2021) and with other reports showing that a small fraction of antibodies target this surface of the spike protein (Voss et al, 2021).…”
Section: Assay Design and Validationsupporting
confidence: 94%
“…Natural RBD mutants included RBD-V483A, RBD-V367F and RBD-G476S that were in circulation in the U.S. in 2020, and a designed triple mutant that disrupts the RBD-ACE2 interaction, N487K, Q493K and N501K in Spike (termed Spike-T hereafter) and RBD (termed RBD-T hereafter; Fig. 1D) (Hattori et al, 2021). These designed mutations disrupt the interaction of RBD with neutralizing antibodies that target the ACE2-interaction surface.…”
Section: Assay Design and Validationmentioning
confidence: 99%
See 3 more Smart Citations